Analysis of the Alignment of OBE-Based Curriculum with the Principles of Sustainable Development Goals in Higher Education - Dede Indra Setiabudi; Syakillah Fi Ismi (Proceeding of the International Conference on Global Education and Learning, 2025)
This study aims to evaluate the extent to which the principles of the Sustainable Development Goals (SDGs) are integrated into the Outcome-Based Education (OBE) curriculum of the Primary School Teacher Education Program (PGMI) at the Al-Zaytun Islamic Institute of Indonesia. Responding to the limited number of empirical curriculum studies linking OBE and sustainability, this research adopts a library research design supported by structured content analysis of curriculum documents, including Graduate Learning Outcomes (CPL), Course Learning Objectives (CPMK), and assessment rubrics. The analytical rubric was developed based on Education for Sustainable Development (ESD) indicators recommended by UNESCO. Findings indicate that only 30% of CPL and 22.7% of CPMK explicitly incorporate SDG values, with the dominant themes being inclusive education, social empathy, and critical thinking. The remaining components either indirectly address sustainability principles or primarily focus on technical pedagogical aspects. This reveals a misalignment between the curriculum’s current structure and the transformative vision of ESD and SDGs. Methodologically, this research contributes by offering a replicable rubric for assessing curriculum sustainability. Conceptually, it establishes a link between the OBE framework and sustainability values within Islamic teacher education. Practically, the findings provide actionable insights for curriculum developers and policymakers to enhance alignment with global sustainability agendas. The study emphasizes the strategic role of PGMI in fostering sustainability-oriented educators and advocates for systemic curriculum reform to produce future teachers equipped with the knowledge, values, and skills necessary to address contemporary global challenges. Strengthening the integration of SDGs within OBE-based curricula is essential for higher education institutions to actively contribute to the realization of a sustainable future.